1980
DOI: 10.3354/meps003041
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Incorporation of Dissolved Amino Acids by Interstitial Turbellaria and Polychaeta and their Dependence on Temperature and Salinity

Abstract: Interstitial meiofauna turbellarians (Haplogonaria syltensis, Nernatoplana coe1ogynoporoides) and polychaetes (Trilobodrilus axi, Hesionides arenaria) from surf-beaten sand beaches are able to absorb dissolved I4C-labelled glycine and aaminoisobutyric acid. In contrast, absorption by the copepod Rhizothrix gracilis is negligible. Uptake has been confirmed by autoradiographic studies, liquid scintillation counting of labelled and combusted animals, and by measurement of the incorporation of labelled glycine int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…), provides an indirect measure of wet mass rather than a direct measure of dry mass, as done here. However, by developing a regression between empirically measured dry mass and the estimated wet mass on the basis of biovolume, we found that, on average, the percentage water weight of parasites (79%) was similar to what we would expect based on morphologically similar free‐living taxa (Schmitt [as cited by Tempel & Westheide ], Edwards & Bohlen ). This suggests that the wet mass measurements generated by combining parasite size with an assumed parasite wet mass tissue density of 1.1 g/mL are likely reasonable.…”
Section: Discussionsupporting
confidence: 56%
“…), provides an indirect measure of wet mass rather than a direct measure of dry mass, as done here. However, by developing a regression between empirically measured dry mass and the estimated wet mass on the basis of biovolume, we found that, on average, the percentage water weight of parasites (79%) was similar to what we would expect based on morphologically similar free‐living taxa (Schmitt [as cited by Tempel & Westheide ], Edwards & Bohlen ). This suggests that the wet mass measurements generated by combining parasite size with an assumed parasite wet mass tissue density of 1.1 g/mL are likely reasonable.…”
Section: Discussionsupporting
confidence: 56%
“…Average values (usually 30 to 80 pm01 dm-3) for DFAA, one of the most relevant organic compounds for transepidermal uptake (Stephens, 1975;Jsrgensen, 1976;Tempel and Westheide, 1980) were mostly higher in the cores monitored here than in other eulittoral or sublittoral sediments. With the exception of a few peak values (244 pnol dm-3), they lay in the range for intertidal mud flats (Stephens, 1975;Costopulos et al, 1979;Jargensen et al, 1980;Jsrgensen et al, 1981), for sandy beaches (Tempel and Westheide, 1980), or for sublittoral areas (Henrichs and Farrington, 1979;Southward et al, 1979).…”
Section: Discussionmentioning
confidence: 78%
“…With the exception of a few peak values (244 pnol dm-3), they lay in the range for intertidal mud flats (Stephens, 1975;Costopulos et al, 1979;Jargensen et al, 1980;Jsrgensen et al, 1981), for sandy beaches (Tempel and Westheide, 1980), or for sublittoral areas (Henrichs and Farrington, 1979;Southward et al, 1979). The concentrations of DFAA found in Flatts Inlet exceeded by a factor of 2 to 3 corresponding data in other carbonate sediments from nearby Bermudian shores (Lyons et al, 1979;Liebezeit, 1980).…”
Section: Discussionmentioning
confidence: 95%
“…Paracatenula species have no mouth but apparently derive nutrition from prokaryotic symbionts occurring in entoderm cells (Ott et al, 1982) . At least two interstitial turbellarians can utilize dissolved amino-acids taken up via the body wall (Tempel & Westheide, 1980) . Turbellaria are eaten by some macrofaunal crustaceans and bivalves (Feller, 1984), by predatory polychaetes and apparently by deposit feeders .…”
Section: Predation By Meiofauna (Including Turbellarians)mentioning
confidence: 99%